Study of Aquatic Sedimentation Using Electromagnetic Modeling in Flood Hazard Mitigation Scheme - Widodo Widodo; M. Rheza Zamani; Sindi Hajah Patimah; Elis Agustiana (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
The accumulation of sediment in aquatic environments can lead to an increase in flood risk due to raised floodplains and water levels. Electromagnetic modeling techniques, such as Time Domain Electromagnetic (TDEM) resistivity or lithological conductivity contrast, can be utilized to detect changes in the subsurface. In this study, we investigated the use of TDEM in flood hazard mitigation schemes by developing a 1-D forward modeling program for the central loop configuration in an aquatic environment using the Adaptive Born Forward Mapping (ABFM) method. The program was tested in various environmental conditions, i.e., freshwater, brackish water, and saltwater, to determine its response. The objective is to prevent natural disasters, particularly flooding caused by sedimentation. The TDEM models can generate images of sediment thickness, providing a sensitive response in saltwater environments and enabling the detection of changes in depth compared to other aquatic environments. Overall, this study demonstrated the potential of TDEM as a valuable tool in flood hazard mitigation schemes.